Analisis Sifat Kimia Velva Terong Ungu (Solanum Melongenal) Dengan Fortifikasi Sari Buah Markisa (Passiflora Edulis Var. Flavicarpa) - Afifudin Ibadi; Wiwik Wahyuni; Laili Hidayati (Jurnal Inovasi Teknologi dan Edukasi Teknik, 2021)
Purple eggplant is a vegetable that is commonly cultivated in Indonesia. Product innovation is needed to increase people's consumption of eggplants, such as being made into Velva. Purple eggplant has the potential to be used as a raw material for making Velva because it has a thick pulp. The processing of Velva can reduce the nutritional content of purple eggplant. The fortification of passion fruit juice in this study is expected to increase the nutritional value of purple eggplant Velva. The research method used a completely randomized design with two repetitions and three levels of concentration of passion fruit juice fortification, namely 10 percent, 20 percent, 30 percent. Observation parameters included vitamin C content, dietary fiber, and antioxidant capacity. The data from the analysis were statistically tested using ANOVA. If a difference is found, then proceed with Duncan's Multiple Range Test (DMRT). Based on the results of the study, the concentration of 30 percent passion fruit juice fortification showed the highest results for the content of vitamin C and total dietary fiber, namely vitamin C 17.144 mg / 100gr and total food fiber of 42.481 percent. The highest IC50 content was obtained from the fortification concentration of 10% passion fruit juice with a value of 92.338 ppm. Terong ungu merupakan sayuran yang sudah umum dibudidayakan di Indonesia. Perlu adanya inovasi produk untuk meningkatkan konsumsi masyarakat terhadap terong, seperti dibuat menjadi velva. Terong ungu berpotensi digunakan sebagai bahan baku pembuatan velva karena memiliki daging buah yang tebal. Proses pengolahan pada velva dapat menurunkan kandungan gizi pada terong ungu. Fortifikasi sari buah markisa pada penelitian ini diharapkan dapat meningkatkan nilai gizi velva terong ungu. Metode penelitian menggunakan Rancangan Acak Lengkap dengan dua kali pengulangan dan tiga tingkatan konsentrasi fortifikasi sari buah markisa, yaitu 10 persen, 20 persen, 30 persen. Parameter pengamatan meliputi kandungan vitamin C, serat pangan, dan kapasitas antioksidan. Data hasil analisis diuji statistik menggunakan ANOVA. Apabila ditemukan perbedaan, kemudian dilanjutkan dengan uji Duncan’s Multiple Range Test (DMRT). Berdasarkan hasil penelitian, konsentrasi fortifikasi sari buah markisa 30 persen menunjukkan hasil tertinggi untuk kandungan vitamin C dan serat pangan total, yaitu vitamin C 17,144 mg/100gr dan serat pangan total 42,481 persen. Kandungan IC50 tertinggi diperoleh dari konsentrasi fortifikasi sari buah markisa 10 persen dengan nilai 92,338 ppm.